Keanekaragaman dan Kerapatan Jenis Lamun di Desa Tontayuo Kecamatan Batudaa Pantai Teluk Tomini - Rika Anggraini; Faizal Kasim; Citra Panigoro (The NIKe Journal, 2025)
Seagrass ecosystem is one of the shallow marine ecosystems that plays an important role in supporting the life and development of organisms in shallow seas, namely as a primary producer, habitat for biota, capturing sediment and nutrients in the waters. This study aims to determine the diversity and density of seagrass species in the waters of Tontayuo Village. This research was conducted in April-August 2022. Observation of the diversity and density of seagrass species used the 1 x 1 meter sample plot method. The research location is divided into three stations based on the presence of seagrass. Data analysis includes density and diversity index. The observation results show that the area of seagrass is 1.2 Ha. Eight species of seagrass found in this area consist of Thalassia hemprichii, Cymodocea serrulata, Syringrodium isoetifolium, Halodule pinifolia, Halodule uninervis, Halophila minor, Halophila ovalis and Cymodocea rotundata. All of these seagrass species have a very dense density. However, the diversity of seagrass species in this area is low.